EXPRESSIONS OF LAGUERRE POLYNOMIALS THROUGH BERNOULLI POLYNOMIALS - Popov, Blagoj S. (Matematichki Bilten, 1998)
The aim of this paper is to obtain an expansion formula of Laguerre polynomials through Bernoulli polynomials.